"Nutrothorax" complicating a misplaced nasogastric feeding tube in a severely ill patient - Aloísio Felipe-Silva; Fernando Peixoto Ferraz de Campos (University of São Paulo, 2012)
Introduction of nasogastric feeding tubes is usually blindly performed and is generally considered a safe procedure. However, the rate of complications of a blind insertion technique varies from 0.3 to 15%, and is usually related to inadvertent insertion of nasogastric tubes into the trachea and distal airways. The main predisposing factors related to tube malpositioning and complications are altered mental status with decreased cough or gag reflex, a preexisting endotracheal tube and severe illness. Complications include severe aspiration pneumonia, hydrothorax, hemothorax, empyema and pneumothorax. The mortality related to misplacement of a nasogastric tube is around 0.1-0.3% of the procedures. This 61-year old female had a history of poor appetite, weight loss, dyspnea and fever. A chest axial computerized tomography showed enlarged mediastinal lymph nodes. Laboratory showed hypercalcemia with normal PTH and hypokalemia. As the patient remained anorectic, a nasogastric feeding tube was placed, through which the administration of enteral diet, by continuous infusion pump, was started. After 12 hours the patient developed dyspnea, hypoxemia and hypotension. During orotracheal intubation, it was disclosed the presence of the nasogastric tube in the trachea as well as the infused diet within the respiratory tract. Autopsy revealed an unusual complication of a nasogastric tube misplacement, which led to a massive collection of enteral nutrition fluid into the pleural space - a "nutrothorax". Additionally, an underlying stage IV anaplastic large cell lymphoma with interstitial lung and bronchial mucosa involvement was diagnosed.